(untitled) (Trabalho & Educação, 2018)
The article presents the results of the theoretical conceptual review, which gave basis to the problem’s constitution and the development of a field research, which purpose was to analyze the nexus between motives and personal senses of the choice of physicians in higher education as professional activity. This review privileged the theoretical contributions of Alexei N. Leontiev, especially his Theory of Activity, the foundations in Marx and Vygotsky that served him for this systematization and the discussion he makes about the correlations between motives of activity and personal senses. ___ O artigo apresenta resultados de revisão teórica conceitual, que deu base à constituição do problema e desenvolvimento de uma pesquisa empírica, cujo propósito foi de analisar os nexos entre motivos e sentidos pessoais da escolha por médicos da docência no ensino superior como atividade profissional. Essa revisão privilegiou as contribuições teóricas de Alexei N. Leontiev, especialmente sua Teoria da Atividade, os fundamentos em Marx e Vygotsky que lhe serviram para essa sistematização e a discussão que ele faz sobre as correlações entre motivos da atividade e sentidos pessoais.